ARTIFICIAL INTELLIGENCE (AI), DIGITAL MARKETING AND POPULARITY ON PURCHASE INTENTIONS FOR VIRTUAL CONCERTS IN KOREAN GIRLBAND AESPA - Fandy Al Ubaidah; Istian Kriya Almanfaluti; Mochamad Rizal Yulianto; Alshaf Pebrianggara (PT ANTIS INTERNATIONAL PUBLISHER, 2025)
Objective: The impact of the Behavioral Control Model, Personal Innovation, and Technology Acceptance on Shopee Online Purchase Interest is examined in this study. Method: Data was gathered from 96 respondents via questionnaires sent to Shopee platform users utilizing a quantitative study design and SmartPLS software. Results: These results show a favorable association between the factors of the Technology Acceptance Model, Personal Innovation, and Behavioral Control, and how these affect Online Purchase Interest. The study's findings emphasize the significance of the Shopee platform's use of the technology acceptance model, consumer creativity, and the application of efficient behavioral management to boost platform users' enthusiasm in making purchases. Novelty: The implications of this research contribute to consumer understanding in the context of online product or service shopping, assisting researchers in developing strategies that can increase customer engagement and satisfaction.